PENGARUH KUALITAS PELAYANAN SISTEM ELEKTRONIK PERPAJAKAN DAN KOMPETENSI PEGAWAI PAJAK PADA KEPUASAN WAJIB PAJAK - Sari, Wulan Sepvita; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
Satisfaction of taxpayer is representation from  harmony between the expectations of the taxpayer and the results obtained from the existence of an  taxation system. The issueabout  service quality of electronic system of taxation is not maximized, allegedlyone of the factors cause dissatisfaction taxpayers while meeting tax obligations. Tax obligations are not fulfilled will be led to declining tax revenues. This Research has purpose to insvestigate the influence of service quality electronic systems of taxation and tax employee competencies in satisfaction WP OP in KPP Pratama Denpasar Timur. The total sample are 100 respondents, method to determine sample isusing accidental sampling. The data collection method is using questionnaire. Mechanical analysis of data used is  multiple linear regression. Outcome from this research is that the service quality of the electronic system oftaxation and tax employee competencies are significant positive effect to the satisfaction of the WP OP.
Keywords: Service quality, electronic system of taxtation, Employee competency, Satisfaction of taxpayer